Capillary Deposition of Complement C4d and C3d in Chinese Renal Allograft Biopsies. (4th March 2015) - Lv, Rong; Zhang, Wei; Han, Fei; Liu, Guangjun; Xie, Wenqing; Chen, Jianghua
Abstract : Background . C3d is a product of both the classic and the alternative complement cascades; however, few studies have addressed the role of C3d in renal biopsies and its relationship with long-term graft survival rate is not very clear. Methods . 94 patients with biopsy-proven acute rejection episodes were included in the study. We investigated the associations between histological findings, clinical examinations, and outcome. Results . The overall prevalence for C4dPTC and C3dPTC was 42.6% and 29.8%. There was a significant association between C3dPTC and C4dPTC (P < 0.001 ). C3dPTC and C4dPTC were related with histological types (P = 0.024 andP < 0.001, resp.). The long-term survival rate for C4dPTC positive transplants was lower than that of C4dPTC negative transplants, but it was not statistic significant in our study (P = 0.150 ). The survival rate of C3dPTC positive group was much lower than the negative group (P = 0.014 ). Patients with double positives for C4dPTC and C3dPTC exhibited the lowest survival rate significantly different from those of the C3dPTC only and C4dPTC only groups (P = 0.01 andP = 0.0037 ). Conclusions . This longitudinal cohort study has demonstrated that C3d deposition in the PTC was closely related to renal dysfunction and pathological changes.